CLASSROOM TEACHER’S VIEWS ABOUT READİNG COMPREHENSION DIFFICULTIES IN TURKISH LESSONS: A QUALITATIVE STUDY - Mustafa KOCAARSLAN (Fırat University, 2019)
The aim of this study is to reveal the classroom teacher’s views and practices in relation to reading comprehension difficulties experienced by students in Turkish lessons. The research was conducted as a descriptive study and designed as a qualitative research. The subjects of this study consisted of twenty-one classroom teachers who were selected by using purposive sampling and participated in this study voluntarily. Semi-structured interview method which is suitable for qualitative research was used for data collection. The data obtained after interviews were analyzed by using descriptive analysis and supported by direct quotations. Reading comprehension difficulties experienced by the students in Turkish lessons and the causes were revealed according to the classroom teacher’s views. Furthermore it was included methods and implementations which have been used by classroom teachers in identifying, removing of reading comprehension difficulties. As a result of research, classroom teachers stated that reading comprehension difficulties encountered by their students as “unable to bring prior knowledge in reading environment”, “inability to synthesize”, inability to make inferences (being not able to use context clues), “unable to cause and effect relationship”, “inability to focus to main meaning in consequence of going into in detail” in Turkish lesson. They reported that the most common difficulty in reading comprehension as “unable to bring background information in reading environment”. When analyzing the data from the research it was determined that reader features leading to difficulties in reading comprehension as “lack of reading habits”, “inadequate vocabulary”, “not giving importance punctuation marks and prosodic reading”,” not using spoken language accurately and effectively”, “giving priority to faster reading”, “attention deficit”, “lack of motivation”,” inability to enjoy reading”, “inability in using the imagination while reading”, “the use of local slang”, lack of prior knowledge” and “mental sluggishness”. Classroom teachers participating in the study expressed that they used a variety of methods / techniques that can be used in improving and evaluating reading comprehension and that they had various applications in this regard in the their classroom. Classroom teachers listed that environmental factors affecting reading comprehension difficulties as “does not support the family for children in the work of reading”, “does not create